Efek Annealing Temperture Terhadap Sifat Magnetik Dan Struktur Multilapisan Tipis Cobalt-Samarium - Erwin E (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Multilayer thin films of cobalt and samarium with the structur of 20[Co (4.2 nm)/Sm (3.8 nm)] have been fabricated using dc magnetron sputtering technique. Crystalline formation due to heat treatment of about 450oC of the sample is responsible for increase of coercivity from 300Oe to 3500 Oe. Due to heat treatment (annealing) of the sample caused the value of the magnetization of the sample decreases. This is due to the formation of none magnetic phase ininterfacial mixing between the layers as a result of inter-diffusion between the layers. Structural properties of as deposited and annealed samples was studied using transmission electron microscope (TEM). Electron diffraction patterns for as deposited sample exhibit diffused rings for samarium reflection however, for the annealed sample of about 450oC for 30 minutes produces sharp diffraction rings. This indicates that alloys of CoSm in interfacial mixing has a crystalline properties. By modifying the annealing temperature and time one can obtain higher value of coercivity of alloy of CoSm between the layers as one of therequirements for higher density magnetic recording media.